(untitled) (World Economics and Finance Bulletin, 2024)
In this paper has been investigated ways of identifying internal and external threats to the financial security of textile enterprises are outlined, the problems of financial security of enterprises are studied, and have been proposed scientific recommendations for improving the efficiency of managing this process.